Translating mathematical representations through cultural contexts: Affective responses of Indonesian preservice teachers - Aprinastuti, Christiyanti; Kovács, Zoltán (Journal on Mathematics Education, 2025)
Research on mathematical representations has predominantly emphasized their cognitive and conceptual benefits; however, limited attention has been given to their emotional dimensions, especially within culturally grounded or ethnomathematical contexts. This gap is critical because emotions play a significant role in shaping preservice teachers’ engagement and long-term attitudes toward mathematics. Addressing this issue, the present study introduces a novel perspective by examining how mathematical representations influence the affective responses of prospective primary teachers when tasks are embedded in cultural practices. Employing a mixed-methods design, the study involved 62 preservice teachers who completed a patterning task based on the Javanese Sedekah Bumi ceremony, followed by a researcher-developed questionnaire measuring enjoyment. The results reveal that 79.03% of participants successfully translated verbal descriptions into graphical forms, reflecting a strong visual preference, and that flexible use of multiple representations (72.54%) enhanced both conceptual understanding and positive emotional engagement. Conversely, reliance on a single representation was associated with lower confidence and reduced enjoyment. Notably, 19.35% of participants explicitly reported that the integration of cultural elements increased their motivation and interest. These findings highlight the potential of culturally embedded mathematical tasks not only to foster representational fluency but also to enrich the affective domain, offering valuable implications for the design of teacher education curricula that promote both cognitive and emotional development in mathematics learning.